Colon Cancer with Streptococcus gallolyticus Aortic Valve Endocarditis: A Missing Link?. (3rd July 2019) - Chime, Chukwunonso; Patel, Harish; Kumar, Kishore; Elwan, Ahmed; Bhandari, Manoj; Ihimoyan, Ariyo
Abstract : Bacterial endocarditis is commonly encountered in clinical practice. Many bacterial species have been implicated; however, Streptococcus gallolyticus species (formerly " bovis ") has driven attention given a historical association with colon cancer. Colonoscopy is recommended in an individual with S. gallolyticus endocarditis or bacteremia to evaluate the possibility of high-grade adenoma or colon cancer. There has been no firm recommendation for prophylactic antibiotics to prevent bacterial endocarditis for patients undergoing endoscopic procedures and postcolonoscopy bacteremia in an individual with an endoscopic procedure indicated for S. gallolyticus bacteremia has not been reported. Studies have been aimed at understanding the association between colon cancer and this bacterial pathogen. There are suggestions that the systemic manifestation of S. gallolyticus, a commensal in the colon premalignant cells, may be further predisposed by patient's immunocompromised status. We present a case of the 72-year-old man with the newly diagnosed multiple myeloma presented with aortic valve endocarditis and S. gallolyticus bacteremia. Colonoscopy revealed colon cancer and high-grade adenoma; few hours after procedure, he presented with Streptococcus mitis bacteremia . In conclusion, our case realigns association of S. gallolyticus to colon cancer, especially in an individual with altered immunity, and is novel to demonstrate the rare association of two distinct bacteria of Streptococcus species associated with cancer. Preendoscopic antibiotics use, though not standard of care, can be considered in the high-risk individual. Altered immunity can be considered the "missing link" inciting bacteremia in individuals with S. gallolyticus -associated colon cancer.